Downregulation of mucosal mast cell activation and immune response in diarrhoea‐irritable bowel syndrome by oral disodium cromoglycate: A pilot study. Issue 6 (1st October 2017) - Lobo, Beatriz; Ramos, Laura; Martínez, Cristina; Guilarte, Mar; González‐Castro, Ana M; Alonso‐Cotoner, Carmen; Pigrau, Marc; de Torres, Inés; Rodiño‐Janeiro, Bruno K; Salvo‐Romero, Eloisa; Fortea, Marina; Pardo‐Camacho, Cristina; et al.
Abstract : Background and goal: Diarrhoea‐predominant irritable bowel syndrome (IBS‐D) exhibits intestinal innate immune and mucosal mast cell (MC) activation. MC stabilisers have been shown to improve IBS symptoms but the mechanism is unclear. Our primary aim was to investigate the effect of oral disodium cromoglycate (DSCG) on jejunal MC activation and specific innate immune signalling pathways in IBS‐D, and secondarily, its potential clinical benefit. Study: Mucosal MC activation (by ultrastructural changes, tryptase release and gene expression) and innate immune signalling (by protein and gene expression) were quantified in jejunal biopsies from healthy (HS; n = 16) and IBS‐D subjects after six months of either treatment with DSCG (600 mg/day, IBS‐D‐DSCG group; n = 18) or without treatment (IBS‐D‐NT group; n = 25). All IBS‐D patients recorded abdominal pain and bowel habits at baseline and in the last 10 days prior to jejunal sampling. Results: IBS‐D‐NT exhibited significant MC activation and over‐expression of immune‐related genes as compared to HS, whereas in IBS‐D‐DSCG MC activity and gene expression were similar to HS. Furthermore, DSCG significantly reduced abdominal pain and improved stool consistency. Conclusion: Oral DSCG modulates mucosal immune activity and improves gut symptoms in IBS‐D patients. Future placebo‐controlled clinical trials are needed for confirmation of clinical benefit of DSCG for IBS‐D.